2011
DOI: 10.3109/1354750x.2011.635804
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of transforming growth factor beta 1 [TGF-β1] and matrix metalloproteinase 9 [MMP-9] in oral squamous cell carcinoma

Abstract: Unlike TGF-β1, MMP-9 might be useful for prognosis determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 25 publications
5
33
2
Order By: Relevance
“…[22][23][24][25] Hernández-Pérez et al [26] found that MMP-14 may be used as a prognosticator in SCC while MMP-2 may be of relevance to tumor progression.…”
Section: Discussionmentioning
confidence: 98%
“…[22][23][24][25] Hernández-Pérez et al [26] found that MMP-14 may be used as a prognosticator in SCC while MMP-2 may be of relevance to tumor progression.…”
Section: Discussionmentioning
confidence: 98%
“…64,65 Wingless-type MMTV integration site family member 5B (WNT5B) knockdown suppresses MMP-10 production and invasion indicating that the WNT signaling pathways can also contribute to invasion. 66,67 Transforming growth factor b (TGFb) can be produced by tumor-associated fibroblasts 68 and induce NF-jB activation 69 and SMAD-dependent MMP production, 70 as well as epithelial to mesenchymal transition (EMT) factors, such as Snail and Slug. [71][72][73][74][75][76] Invasion is stimulated by hypoxia in a Notch-dependent fashion.…”
Section: Cell Surface Receptors Influence Invasivementioning
confidence: 99%
“…Numerous studies have demonstrated a direct link between TGFβ/NF-κB signaling and MMP overexpression in various cancers [35][38]. MMPs, a family of zinc-dependent endopeptidases that catalyze the disintegration of the ECM and basement membrane play a pivotal role in tumor invasion and angiogenesis [39].…”
Section: Discussionmentioning
confidence: 99%